World Christianity 2025: Regional Perspectives - Zurlo, Gina A. (International bulletin of mission research, 2025)
This article marks the 41st year of including statistical information on World Christianity and mission in the IBMR. This year’s focus is geographical, covering major religious trends in Africa, Asia, Europe, Latin America, Northern America, and Oceania over the last 125 years. This year’s article includes the Middle East, which is formed by countries in Northern Africa and Western Asia. In 2025, the Global South is home to 69% of all Christians in the world, projected to reach 78% by 2050. Africa became the continent with the most Christians in 2018, passing Latin America (which passed Europe in 2014).